Electrochemical Deposition by Design of Metal Nanostructures - Monaico, Ed.; Monaico, E. I.; Ursaki, V. V.; Tiginyanu, I. M.; Nielsch, Kornelius (Surface Engineering and Applied Electrochemistry, 2019)
Abstract –: We report on the application of specially-designed masks for the purpose of electrochemical etching of InP single crystals which enables one to change in a controlled fashion the direction of propagation of pores, including those propagating in directions parallel to the top surface of substrates. The fabricated templates have been used to electrochemically deposit metallic nanostructures along predefined directions and to develop two-dimensional arrays of metallic nanotubes or nanowires embedded in semiconductor matrices.
CRIS-Team Scopus Importer:2022-04-14
Keywords: arrays of nanopores; Au nanodots; controlled electrodeposition; electroplating; porous semiconductor